The pictorial fit-frail scale malay version (PFFS-M): predictive validity testing in Malaysian primary care - Ahip, Sally Suriani; Theou, O.; Shariff-Ghazali, S.; Samad, A.A.; Lukas, S.; Mustapha, U.K.; Visvanathan, R. (Serdi-Editions, 2024)
The purpose of this study was to evaluate the association between Pictorial Fit Frail Scale-Malay version (PFFS-M) and adverse outcomes, such as falls, new disability, hospitalisation, nursing home placement, and/or mortality, in patients aged 60 and older attending Malaysian public primary care clinics. We assessed the baseline PFFS-M levels of 197 patients contactable by phone at 18 months to determine the presence of adverse outcomes. 26 patients (13.2%) reported at least one adverse outcome, including five (2.5%) who fell, three (1.5%) who became disabled and homebound, 15 (7.6%) who were hospitalized, and three (1.5%) who died. Using binary multivariable logistic regression adjusted for age and gender, we found that patients who were at-risk of frailty and frail at baseline were associated with 5.97(95% CI [1.89–18.91]; P=0.002) and 6.13 (95% CI [1.86–20.24]; P= 0.003) times higher risk of developing adverse outcomes at 18 months, respectively, than patients who were not frail. The PFFS-M was associated with adverse outcomes. © 2023, The Author(s).